2007
DOI: 10.7202/032962ar
|View full text |Cite
|
Sign up to set email alerts
|

Regional Stratigraphic Framework of Surficial Sediments and Bedrock Beneath Lake Ontario

Abstract: La néotectonique de la région des Grands Lacs Volume 47, numéro 3, 1993 URI : id.erudit.org/iderudit/032962ar

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…All radiocarbon dates were converted to calibrated ages using INTCAL09 (Reimer et al, 2009). Additional information used to construct the age-depth model included pollen stratigraphy (Carmichael et al, 1990;McAndrews, 1994;Pippert et al, 1996), seismic stratigraphy (Hutchinson et al, 1993), magnetic properties (Carmichael et al, 1990) and previously reported radiocarbon dates (Schroeder and Bada, 1978;Silliman et al, 1996;Anderson and Lewis, 2012) (Table 2). These data were combined to produce a nonBayesian, linear interpolated age-depth model using the computer program CLAM (Blaauw, 2010), which provides a probabilistic age range for each depth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All radiocarbon dates were converted to calibrated ages using INTCAL09 (Reimer et al, 2009). Additional information used to construct the age-depth model included pollen stratigraphy (Carmichael et al, 1990;McAndrews, 1994;Pippert et al, 1996), seismic stratigraphy (Hutchinson et al, 1993), magnetic properties (Carmichael et al, 1990) and previously reported radiocarbon dates (Schroeder and Bada, 1978;Silliman et al, 1996;Anderson and Lewis, 2012) (Table 2). These data were combined to produce a nonBayesian, linear interpolated age-depth model using the computer program CLAM (Blaauw, 2010), which provides a probabilistic age range for each depth.…”
Section: Methodsmentioning
confidence: 99%
“…All radiocarbon dates were converted to calibrated ages by CLAM using INTCAL09 (Reimer et al, 2009). Three radiocarbon dates were used along with information gathered from previous studies of Lake Ontario to establish the chronology (Carmichael et al, 1990;Hutchinson et al, 1993;McAndrews, 1994;Pippert et al, 1996;Silliman et al, 1996;Anderson and Lewis, 2012). Table 1 Radiocarbon dates were obtained at the University of Arizona AMS Laboratory in Tucson, AZ, USA.…”
Section: Ostracode Valve and Clam Shell Carbon-isotope Compositionsmentioning
confidence: 99%